2018
DOI: 10.1111/nyas.13862
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic influences on brain function: implications for health

Abstract: Socioeconomic-based disparities in physical health outcomes are well established, with individuals from lower socioeconomic status (SES) backgrounds being more likely to experience chronic disease morbidity and early mortality compared to those from higher SES strata. While numerous studies in recent decades have focused on understanding the contextual, psychosocial, and biological mechanisms linking SES and health, the neural pathways that contribute to this relationship are currently underinvestigated. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 111 publications
(208 reference statements)
1
23
0
Order By: Relevance
“…Despite participants having the same high health status, the observed SMG volume effects involving different SES levels may be related to one's subjective experience in the social environment (Muscatell 2018). For example, recent evidence revealed a SES-based difference in social distancing behavior during the COVID-19 pandemic (Weill et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite participants having the same high health status, the observed SMG volume effects involving different SES levels may be related to one's subjective experience in the social environment (Muscatell 2018). For example, recent evidence revealed a SES-based difference in social distancing behavior during the COVID-19 pandemic (Weill et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Disproportionately worse health outcomes were reported in low-SES individuals (Patel et al 2020). SES is a multifactorial construct that tracks dimensions of lifestyle, habitus, and world view, such as economic resources, occupational prestige and education attainment (Farah, 2017;Muscatell, 2018). A variety of studies showed that the "better off" an individual is as captured by common SES measures, the lower their risk to incur detrimental mental and physical health outcomes (Nancy E. Adler & Newman, 2002;Braveman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SES was operationalized as a composite score of total years of formal education and household income over the past 12 months. Because education and income are salient indicators of SES [6,7] and national data demonstrates weak-moderate correlations between these measures [24], investigators routinely use a composite index of SES [3,20,25,26]. Similar to previous research, education and income were categorized into approximately equal tertiles (education: 1 = � 12; 2 = 13-16, 3 = � 17; income: 1 = � 49,999; 2 = 50,000-99,999; 3 = � 100,000) and were summed to create a SES score which ranged from 2 (low SES) to 6 (high SES) [26].…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…Importantly, lifestyle factors associated with SES have shown to influence brain volume [14][15][16] and dementia risk [17][18][19]. Recent research suggests SES may be related to alterations in brain health [20][21][22], however, prior studies have not investigated modifiable lifestyle factors that may contribute to the observed associations.…”
Section: Introductionmentioning
confidence: 99%